Fenomena Aplikasi Tiktok Terhadap Perkembangan Sosial Emosional Anak - Fachrul Ramadhan, Muhammad; Ulpi, Wahyuni; Yusuf, Muhammad (JURUSAN PENDIDIKAN GURU PENDIDIKAN ANAK USIA DINI, 2023)
This study aims to determine the impact of using the Tiktok application on children's social-emotional development. This study used qualitative techniques with data collection conducted by interviewing the parents of the four subjects. From the results of research on the four subjects, namely the first, second and fourth subjects, the use of the Tiktok application had a negative impact on their social-emotional development, while the third subject, the Tiktok application had a good impact on their social-emotional development. The conclusions obtained from the four subjects of the Tiktok application have a negative impact on children's socio-emotional development. In this case the role of parents is very important in maintaining children's development including social emotional development, Parents must supervise the use of Tiktok in children so that children don't get addicted to using the Tiktok application. In this case, parents must be good at dividing time and limiting/forbidding children from frequently opening the tiktok application and being diverted from other fun activities at home such as watching TV and even better if their activities are outside the home, such as instructing children to play outside the home together. her friends.